Distribution of the Cabbage Whitefly in Ukraine - Tkalenko, Yu.; Shyta, O. (Quarantine and plant protection, 2025)
Goal. To analyze the dynamics of the spread of the cabbage whitefly (Aleyrodes proletella L.) in Ukraine based on data from the State Service of Ukraine on Food Safety and Consumer Protection, literature sources, and our own observations. Methods. Information-analytical (collection and analysis of materials); field — monitoring of the phytophagous insect on the farm «Zlahoda» (Kyiv region, Bila Tserkva district) in 2022—2024; laboratory — identification of the pest in the Laboratory of Pesticide Application Technology, Institute of Plant Protection of NAAS (IPP NAAS). Results. The cabbage whitefly (Aleyrodes proletella L.) is a polyphagous pest with a high reproduction rate, developing 5—6 full generations during the growing season depending on weather conditions. It infests many crops belonging to 12 botanical families, but the primary hosts are plants of the family Brassicaceae. According to the conducted studies and the data of the State Service of Ukraine on Food Safety and Consumer Protection, the development of the cabbage whitefly was recorded in Ukraine during 2016—2024. The pest was first detected in 2016 in the western regions; in 2022 it was already found in 13 regions, and by 2024 the phytophagous insect had spread across all regions of Ukraine. Conclusions. As of January 1, 2025, the range of the cabbage whitefly in Ukraine covers all zones: Polissia, Forest-Steppe, and Steppe, and its distribution continues to expand. Monitoring revealed that in the Forest-Steppe zone the pest infests all types of cabbage: Chinese cabbage, savoy, Brussels sprouts, cauliflower, broccoli, white cabbage, and red cabbage; among weeds — wild radish, common charlock, field mustard, and shepherd’s purse. Notably, it does not damage plants of the Cucurbitaceae family, including pumpkin, cucumber, melon, squash, watermelon, and pattypan squash.